Polyphosphate Kinase 1 Is a Pathogenesis Determinant in Enterohemorrhagic Escherichia coli O157:H7 - Du, Yanli; Wang, Xiangyu; Han, Zongli; Hua, Ying; Yan, Kaina; Zhang, Bao; Zhao, Wei; Wan, Chengsong (Frontiers in Microbiology, 2021)
Aim: The ppk1 gene encodes polyphosphate kinase (PPK1), which is the major catalytic enzyme that Escherichia coli utilizes to synthesize inorganic polyphosphate (polyP). The aim of this study was to explore the role of PPK1 in the pathogenesis of Enterohemorrhagic E. coli O157:H7 (EHEC O157:H7). Materials & methods: An isogenic in-frame ppk1 deletion mutant (Δppk1) and ppk1 complemented mutant (Cppk1) were constructed and characterized in comparison to wild-type (WT) EHEC O157:H7 strain EDL933w by Gram staining and growth curve analysis. Survival rates under heat stress and acid tolerance, both of which the bacteria would face during pathogenesis, were compared among the three strains. LoVo cells and a murine model of intestinal colitis were used as the in vitro and in vivo models, respectively, to evaluate the effect of PPK1 on adhesion and invasion during the process of pathogenesis. Real-time reverse-transcription PCR of regulatory gene rpoS, adhesion gene eae, and toxin genes stx1 and stx2 was carried out to corroborate the results from the in vitro and in vivo models. Results: The ppk1 deletion mutant exhibited disrupted polyP levels, but not morphology and growth characteristics. The survival rate of the Δppk1 strain under stringent environmental conditions was lower as compared with WT and Cppk1. The in vitro assays showed that deletion of the ppk1 gene reduced the adhesion, formation of attaching and effacing (A/E) lesions, and invasive ability of EHEC O157:H7. Moreover, the virulence of the Δppk1 in BALB/c mice was weaker as compared with the other two strains. Additionally, mRNA expression of rpoS, eae, stx1 and stx2 were consistent with the in vitro and in vivo results. Conclusion: EHEC O157:H7 requires PPK1 for both survival under harsh environmental conditions and virulence in vivo.